Empowering Indonesian Language Teachers' Digital Competence through Community-Based Padlet Training: A Comprehensive Mixed-Methods Action Research Study on L1 Writing Instruction - Amira Deani; Ghina’a Jayanthi Putri; Andiana Perizga; Elvan Yudianda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid digitalization of education demands that Indonesian language teachers strengthen their digital competencies, especially in developing L1 writing skills through innovative teaching strategies. This study examines the impact of a community-based professional development program centered on Padlet integration for Indonesian language instruction. Utilizing a convergent mixed-methods action research design, 29 senior high school teachers in Pekanbaru, Riau Province, participated in a two-day intensive training, followed by six weeks of classroom implementation and ongoing mentoring. Data were collected through pre- and post-intervention assessments using the DigCompEdu Check-in instrument, lesson plan quality rubrics, classroom observation protocols, analysis of a student writing corpus (N = 472), and semi-structured interviews. Results indicated significant improvements across all measured outcomes. Teachers achieved notable gains in digital competence (ΔM = +12.83, p < .001, d = 1.24), lesson plan quality (ΔM = +2.23, p < .01, d = 0.67), and classroom implementation. Student writing performance also improved substantially (ΔM = +8.99, p < .001, d = 0.73), with increased lexical diversity, cohesion, and collaborative engagement. Qualitative data highlighted enhanced teacher confidence, ongoing peer collaboration, and improved pedagogical practices. The findings demonstrate that community-based Padlet training effectively elevates digital competence and transforms L1 writing instruction, offering empirical support for scalable professional development models that blend digital tools with pedagogical innovation in Indonesian education.